Expediente e apresentação da edição - Fonseca, Janete Rosa da; Bueno, Helen Paola Vieira; Siebiger, Ralf Hermes (Eventos Pedagógicos, 2025)
Expediente e apresentação da edição - v. 16, n. 1, jan./jun. 2025.